Monetary Dialogue 2009–2014: Looking Backward, Looking Forward - Sylvester Eijffinger (Credit and Capital Markets – Kredit und Kapital, 2015)
When comparing the transparency of the ECB now with the transparency of the ECB about one decade ago, we notice that transparency still can be improved in a few ways. In particular the disclosure related to the ways decisions are reached and the disclosure on its policy (what is the envisioned path of policy?) could be improved. We call for action and in particular we suggest to release minutes and voting records, while also engaging in more explicit and concrete forward guidance. At the same time, we call for a reflection on the institutional setup of the ECB. This is less urgent than the reform with respect to transparency, but in the medium term a necessary exercise. We believe that also in the 8th term of the European Parliament, the Monetary Dialogue will have a role in spurring the debate and possibly influencing the ECB, as it has done in the past. – – Monetärer Dialog 2009–2014: Ein Rückblick und eine Vorausschau Wenn man die jetzige Transparenz der EZB mit der von vor einem Jahrzehnt vergleicht, dann stellt man fest, dass diese immer noch in einigen Punkten verbesserungswürdig ist. Insbesondere sollte verstärkt offengelegt werden wie die Entscheidungsfindung vonstattengeht und welche Politik verfolgt wird (wie stellt sich die EZB den zukünftigen Verlauf ihrer Politik vor?). Wir schlagen zur Verbesserung vor, dass ausführliche Protokolle und auch Wahlergebnisse veröffentlicht werden. Gleichermaßen soll die Vorausschau auf zukünftige Politiken ("forward guidance") expliziter erläutert werden. Zur gleichen Zeit rufen wir dazu auf, dass der institutionelle Rahmen der EZB überdacht wird. Dies ist zwar weniger dringend im Vergleich zu einer größeren Transparenz, aber auf mittlere Sicht dennoch notwendig. Wir glauben außerdem, dass in der achten Legislaturperiode des Europäischen Parlaments der monetäre Dialog weiterhin die Debatte befeuern wird und damit Einfluss auf die EZB nehmen kann.
Keywords: E58; G20; O11; 330; Central Bank Transparency; Central Bank Communication; Macroeconomic Policy